Endovascular stroke treatment now and then-procedural and clinical effectiveness and safety of different mechanical thrombectomy techniques over time - Von Gadow, Niels; Nikoubashman, Omid; Freiherr, Jessica; Block, Frank; Reich, Arno; Fesl, Gunther; Wiesmann, Martin (Quantitative Imaging in Medicine and Surgery, 2017)
Background: The most essential development in endovascular stroke treatment (EST) was the shift from intra-arterial thrombolysis to endovascular thrombectomy with dedicated thrombectomy devices, most notably the introduction of stent-retrievers. We evaluated procedural and clinical effectiveness and safety of different EST techniques over time.Methods: We retrospectively analyzed EST cases that were treated by the same interventionalist before (n=36) and after (n=50) stent-retrievers were established as the treatment device of first choice. EST techniques in the first cohort comprised intra-arterial thrombolysis (n=24), manual thrombus aspiration (n=15), the use of the Penumbra thrombectomy system (n=13) and the Phenox clot retriever (n=3), intracranial stenting (n=10), and EST with stent-retrievers as a salvage procedure (n=11). In the second cohort, EST with stent-retrievers was the treatment option of first choice (n=47). Intra-arterial thrombolysis (n=15) and stenting of the occluded vessel (n=1) were performed, whenever EST with stent-retrievers failed.Results: In both cohorts, revascularization rates (TICI =2b) were high (91.7% and 86.0%, respectively). A significantly lower number of interventional techniques per case were required in the second cohort (mean +/- SD, 1.4 +/- 0.5 vs. 2.1 +/- 0.9, P<0.001). Recanalization was achieved almost twice as fast in the second cohort (85 vs. 163 minutes on average, P<0.001). The rate of patients achieving good functional outcome (mRS =2) was higher in the second cohort (40.0% vs. 22.2%, P=0.083).Conclusions: Our findings imply that when stent-retrievers were established as first-line the treatment device a significantly lower number of interventional techniques per case were required and recanalization was achieved almost twice as fast.
Keywords: Endovascular stroke treatment (EST); interventional; revascularization; stent-retriever